ANALYSIS TYPE OF ROAD DAMAGE IN THE NATIONAL ROAD TEUKU UMAR TUBAN - Richo Ardidarmawan Mintiya (Jurnal Proyek Teknik Sipil, 2022)
The road is an object that can help humans in their lives. One example is that roads can be a link between one place and another, no wonder there are often road damages due to excessive vehicle loads. To overcome it all, it is necessary to have an accurate maintenance to make the road can be used according to the age of the plan. One of the roads that suffered damage wasTeuku Umar Road Tuban, where on this road there were several damages at several points so that the driver had to be more careful to cross this road